The structural, mechanical, and biological variation of silica bioglasses obtained by different sintering temperatures - Sarmast Sh, M.; Dayang Radiah, A. B.; Hoey, D. A.; Abdullah, N. (Springer, 2024)
The challenges of forming a crystalline phase within 45S5 Bioglass® (45% SiO2-24.5% CaO-24.5% Na2O-6% P2O5 mol%) and its subsequent influence on the bioactivity of the bioglass were studied in this research. Bioglasses were sintered at 1400, 750, and 550 °C, using both melting and sol-gel methods. The different responses of bioglasses to different sintering temperatures were revealed. Particularly, increased crystallinity was observed in sol-gel-derived bioglass sintered at 750 °C, indicating a denser and more ordered structure. This crystalline architecture facilitated enhanced bioactivity, as demonstrated by increased hydroxyapatite deposition when immersed in simulated body fluid (SBF). Furthermore, superior mechanical properties and biocompatibility were achieved with this temperature regime, making it a prime candidate for bone regeneration applications. The bioglass sintered at 750 °C exhibited an accelerated degradation rate associated with its porosity, potentially contributing to faster material resorption in vivo. Its antibacterial efficacy against E. coli and S. aureus was also noted, and in vitro studies with MTT assay confirmed that the optimized sol-gel bioglass meets biocompatibility standards. These findings highlight the potential of fine-tuning the sintering temperature to modulate the crystallinity of bioglasses, thereby enhancing their application scope in bone tissue engineering.